2012
DOI: 10.1177/0022034512452278
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial on Fluorides and Sealants for Fissure Caries Prevention

Abstract: To investigate the effectiveness of topical fluorides in preventing fissure caries, we conducted a randomized controlled trial with parallel groups. In total, 501 children (1,539 molars, 3,078 sites), mean age 9.1 years, who had at least one sound permanent first molar with deep fissures or fissures with signs of early caries were recruited. They were randomly allocated among four groups: (1) resin sealant, single placement; (2) 5% NaF varnish, semi-annual application; (3) 38% silver diamine fluoride (SDF) sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
175
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(194 citation statements)
references
References 31 publications
5
175
0
14
Order By: Relevance
“…61,[66][67][68] In their 2016 review of these studies, Ahovuo-Saloranta et al 16 said that it was not possible to reach conclusions about whether to apply FS or FV to the occlusal surfaces of permanent molars to best effect. The clinical outcomes from the current trial suggest that there is no significant difference in the clinical outcome, irrespective of whether FS or FV is used.…”
Section: What Other Studies Foundmentioning
confidence: 99%
“…61,[66][67][68] In their 2016 review of these studies, Ahovuo-Saloranta et al 16 said that it was not possible to reach conclusions about whether to apply FS or FV to the occlusal surfaces of permanent molars to best effect. The clinical outcomes from the current trial suggest that there is no significant difference in the clinical outcome, irrespective of whether FS or FV is used.…”
Section: What Other Studies Foundmentioning
confidence: 99%
“…In the present study, no significant difference in the cumulative survival of free-pit and fissure caries was found between Fuji Triage and Clinpro sealants. Similarly, a field study found no significant difference in the cumulative survival of pit and fissure caries between glass-ionomer and resin-based sealants after two years 30) . Another study reported no significant difference in caries incidence between glass-ionomer and resin-based sealants 33) .…”
Section: Discussionmentioning
confidence: 95%
“…Possibility effect of topical fluoride on the effectiveness of sealants in fissure caries prevention might exist. In addition, both sealant recharge fluoride from the topical fluoride which may increase the caries-preventive effect of both the sealants 29,30) . However, in the current study, no difference in caries-preventive effect between the two sealants was observed as the topical fluoride application was applied to all children and balanced by the same type and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…According to researchers, this product forms a chemical seal with obliteration of dentinal tubules, and the resulting materials -calcium fluoride, silver phosphate and silver proteinate -covering both organic and inorganic parts [29][30][31]. In a 24-month study addressing decay on 1491 molars, it was found the resin sealant Clinpro ® achieved better results in comparison to silver diamine fluoride at a concentration of 38% [32]. A similar result was found in the present investigation when comparing the number of carious lesions in teeth sealed with the resin sealant Alpha Seal ® or Vitremer ® to those sealed with silver diamine fluoride.…”
Section: Discussionmentioning
confidence: 99%